Incidence of procrastination on the academic performance of the subject of Chemistry - Simbaña-Farinango, Lizeth (2024)
Procrastination is the intentional delay of an activity. This action has negative effects on education and society. In the case of students in the academic field, it can have an impact on their performance during their study activities. During the research, the causes of procrastination in learning the subject of chemistry were determined, and subsequently its effects on the subject were verified. The research presented a qualitative-quantitative paradigm with correlational research, and likewise with a socio-educational approach. Techniques such as interview and survey were used to identify the various causes of procrastination. It should be mentioned that the statistical analysis was carried out based on the comparison of the types of procrastination with the academic performance of the first semester. The research presents a negative inverse correlation in passive procrastination, a value of -344 was obtained in Pearson's r and in Bilateral sig. a value of 0.001. Likewise, in decisional procrastination, Pearson's r obtained a value of -221 and in the Bilateral sig. 0.015. In other words, in both cases procrastination has a negative impact on academic performance in the subject of Chemistry. The survey results showed that the main causes of procrastination were emotional stability along with the use of social networks and technological devices. Procrastination is an involuntary act that currently affects the academic performance of students.